Sex-Specific Autonomic Responses to Acute Resistance Exercise - Humm, Stacie M. (Medicina (Kaunas), 2021)
Background and Objectives: Acute resistance exercise (RE) reduces vagal modulation and increases sympathovagal balance, which increases the risk for arrythmias. Few studies have examined sex differences in autonomic modulation after acute RE. The purpose of this investigation was to examine sex-specific responses to acute RE on autonomic modulation. Materials and Methods: Twenty-one resistance-trained individuals (men n = 11, women n = 10) between the ages of 19 and 25 y were analyzed for autonomic modulation in response to acute RE and a control (CON). Measures of autonomic modulation were collected at rest, 15 (R15), and 30 (R30) min following both conditions. Heart rate (HR), log transformed root mean square of successive differences (lnRMSSD), total power (lnTP), low-frequency power (lnLF), high-frequency power (lnHF), sample entropy (SampEn), and Lempel-Ziv entropy (LZEn) were measured at all time points. A three-way repeated analysis of variance (ANOVA) was used to analyze sex (men, women) across condition (RE, CON) and time (Rest, R15, R30). Results: The results are similar for all heart rate variability (HRV) variables at rest for both conditions (RE, CON). SampEn was significantly higher in men compared to women at rest for both conditions (p = 0.03), with no differences in LZEn (p > 0.05). There were no significant (p > 0.05) three-way interactions on any variables. Condition by time interactions demonstrated that both sexes increase in HR (p = 0.0001) and lnLF/HF ratio (p = 0.001), but decreases in lnRMSSD (p = 0.0001), lnTP (p < 0.0001), lnLF (p < 0.0001), lnHF (p = 0.0001), and LZEn (p = 0.009) at R15 and R30 compared to rest following acute RE and were different from CON. Condition by time interaction (p = 0.017) demonstrated that SampEn was attenuated at R15 compared to rest, and the CON, but not R30 following acute RE. Conclusion: Although SampEn is more complex at rest in men compared to women, autonomic modulation responses between sexes following acute RE appear to be similar.